Characteristics of monsoonal precipitating cloud systems over the Indian subcontinent derived from weather radar data. (4th October 2018) - Sindhu, Kapil Dev; Bhat, G. S.
Abstract : The convective area within a mesoscale convective system (MCS) contains intense convective cells or storms which themselves could be made of a single cumulonimbus cloud or several of them joined together. Interconnection between MCS evolution and storms has not been reported previously. We address this gap area by using the Doppler Weather Radar (DWR) data collected at four stations in India during the summer monsoon season of 2013. The four DWR locations selected have different climates ranging from coastal to semi‐arid. Storm is defined as a set of contiguous radar pixels in three‐dimensional space with a reflectivity threshold of 30 dBZ and the threshold criterion is satisfied in a volume of at least 50 km 3 . Monsoonal MCSs contain a few to more than 20 storms depending on geographic location and MCS life stage. The average area of storms ranges from 13 to 170 km 2 while storm heights mostly lie between 6 and 10 km. The growth stage of an MCS is characterized by a rapid increase in the number of storms, while their number and average area decrease in the dissipation stage. Storms occupy 30–70% of the convective area within an MCS and contribute 90–97% of the convective precipitation at any given instant. Thus, a few to several cumulonimbus clouds grouped together in a contiguous manner matter most for convective precipitation, making storm scale an important scale in the hierarchy of scales in tropical deep convective cloud systems. This has implications for cumulus parametrization as well as planning satellite payloads for observing precipitation. Abstract : (a) Geo‐locations of IMD's S‐band DWRs. Dots show DWR locations and the outer circles depict radar range of 150 km. Background is USGS global 30 arc‐second terrain elevation. DWR stations: HYD‐Hyderabad, KOL‐Kolkata, NGP‐Nagpur and PTL‐Patiala. The inset shows latitude–longitude and elevation of DWR stations. (b) June to September average rainfall (cm) based on 0.5° × 0.5° gridded rainfall dataset of IMD and for the period 1951 to 2003. High precipitation along the west coast of India and in northeast India is associated with orography. The area approximately to the north of 18°N and southward of the Himalayas receives a major fraction of seasonal precipitation from monsoon synoptic systems, namely monsoon lows and depressions, and is called the monsoon zone (Gadgil, 2003)